Elucidating risk mechanisms of gene-environment interactions on pediatric anxiety: integrating findings from neuroscience. - Lau, J; Pine, D (2008)
Recent findings of gene-environment interaction on child and adolescent anxiety generate interest in mechanisms through which genetic risks are expressed. Current findings from neuroscience suggest avenues for exploring putative mechanisms. Specifically recent documentations of abnormality in brain function among anxious adolescents may reflect the end-result of gene expression. In turn these inherited predispositions may increase the likelihood of psychopathology in the presence of stress. The aim of the current article is to consider putative mechanisms reflecting genetic sensitivity to the environment (G x E). Thus we review data implicating biased processing of threat information and anomalies in brain circuitry in the expression of pediatric anxiety. These data suggest that links across development among genes, brain, psychological processes, and behavior are far from established. Accordingly, the article proposes strategies for examining these links. Exploring these relationships during development is crucial, given that these early life processes may potentially shape longer-term patterns of emotional behavior, and therefore life-long trajectories of anxiety.